Correlation analysis of PGC-1β, HIF-1α and RETN with the degree of joint destruction in gouty arthritis: PGC-1β, HIF-1α and RETN in gouty arthritis - Bian, Jian; Zhang, Jianguo; Zhang, Bo; Shi, Hongfei (Journal of Medical Biochemistry, 2025)
Objective: To investigate the expression levels of resistin (RETN), hypoxia-inducible factor-1 α (HIF-1α), and peroxisome proliferator-activated receptor γ coactivator-1β (PGC-1β). in gouty arthritis (GA) patients and to analyze their correlations with the degree of joint destruction.Methods: The GA group consisted of 134 GA patients who were admitted to the hospital between January 2023 and October 2024, while the control group consisted of 134 healthy patients who were examined physically in the hospital over the same time period. Serum PGC-1β, HIF-1α, and RETN expression levels were compared. The expression levels of PGC-1β, HIF-1α and RETN in the serum and synovial fluid of patients with different clinical characteristics in the GA group were compared. The degree of joint destruction was divided into 78 cases in the severe GA subgroup and 56 cases in the mild GA subgroup according to the VAS score of the chief complaint pain scale. Compared with PGC-1β, HIF-1α, RETN, and bone destruction factors [β-crosslinking degradation products (β-CTX), tartrate-resistant acid phosphatase-5b (TRACP5b), and nuclear factor κB receptor activator ligand (RANKL)], and inflammatory factors with different degrees of joint destruction, the expression levels of -1β (IL-1β) were analyzed, and the correlations between PGC-1β, HIF-1α, and RETN in serum and synovial fluid and the degree of joint destruction, bone destruction factors, and inflammatory factors were analyzed.Results: The expression level of serum PGC-1β in the GA group was lower than that in the control group, while the expression levels of serum HIF-1α and RETN were greater than those in the control group (P
Keywords: PGC-1β; HIF-1α; RETN; Joint destruction; Gouty arthritis; Correlation analysis